Nisin—A Promising Antimicrobial Compound from Lactic Acid Bacteria - Chen, Guanchong (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Nisin is a classical bacteriocin consisting of thirty-four amino acid residues and undergoing a high degree of post-translational modification to form a unique pentacyclic structure. Nisin is mainly synthesised by lactic acid bacteria. Under natural conditions, it exhibits strong antibacterial activity against Gram-positive organisms and, when combined with chelating agents, is effective against Gram-negative organisms. An excellent safety profile, low cytotoxicity and slow development of resistance are additional benefits. Currently, the application of nisin is focused on food preservation. This is due to the fact that nisin is naturally present in a wide range of historical fermented foods and its safety is fully guaranteed. With the continuous development of bacterial drug resistance and the consequent demand for new anti-infective drugs, its biomedical applications are being actively explored. However, due to the problems of drug stability, safety, and in vivo activity, there is still a certain distance from clinical application. In this paper, the author summarized the structure, biosynthetic mechanism, applications, and possible research directions of nisin.